THE ENSURING FUNCTIONAL INTERCHANGEABILITY WHEN FORMING THE CONTROL COMPLEX OF INDICATORS OF THE INITIAL CONDITION OF THE CONSUMER OF SPORTS AND IMPROVING SERVICES - A. S. Khorloohiyn; P. S. Serenkov; V. M. Romanchack (Приборы и методы измерений)
One of key elements of an engineering component quality management system of process of provision of sports and improving services in gyms is the subsystem of diagnostics of physical client state. The aim of the study was to increase in efficiency of functioning of a quality management system of process of provision of sports and improving services in gyms due to development of techniques of incorrect estimation of the initial client state.The task of formation of a complex of indices of the initial status by criterion of necessary informtiveness is formulated. The principle of the functional interchangeability as a methodological basis for its decision is reasonable. The hierarchical structure of an integral assessment of the initial client state of gym is offered. On its basis the hierarchical model of rating of informtiveness of a complex of the single (measured) indices, the providing objectivity of an integral assessment of the initial status is developed. The correctness of model is provided at the expense of a formulation of a complex of assumptions and original technology of application of different methods of expert estimation.The result of simulation of informtiveness of an integral assessment of the initial client state for a specific type of service and the purposes of physical enhancement includes: 1) library of sets of single indices, for each of which the technique and a monitoring aid, and also an informtiveness assessment in points, 2) the rules of support of the functional interchangeability of alternative complexes of indices by criterion of sufficiency of informtiveness of a complex based on additive models and the accepted restrictions is defined.The concept of a technique of formation of a complex of the measured and (or) evaluated indices of the initial client state for the specific type of sports and improving service adapted under material opportunities of gym on the one hand, and responding to criterion of necessary informtiveness and the principle of the functional interchangeability, on the other hand is offered.